Comparative Analysis of Quality of Service (QoS) on WLAN Network Bandwidth Management using HTB Method with PCQ - Kusbandono, Hendrik; Lestariningsih, Tri; Septianto, Tri (East Asian Journal of Multidisciplinary Research, 2024)
This study explores bandwidth management on WLAN networks using Hierarchical Token Bucket (HTB) and Per Connection Queue (PCQ) methods to optimize Quality of Service (QoS). With the growing role of IT in both business and public sectors and increasing WLAN access, effective bandwidth management has become crucial to prevent certain users from monopolizing bandwidth for upload or download activities. The research involves data collection through observation and literature review, designing a network topology, implementing bandwidth management using HTB and PCQ, and analyzing performance with QoS parameters: throughput, delay, jitter, and packet loss. The results show that the HTB method achieves an average throughput of 97%, a delay of 98 ms, a jitter of 77 ms, and no packet loss, making it ideal for networks requiring priority-based bandwidth allocation for performance-sensitive applications. In contrast, the PCQ method yields an average throughput of 93.5%, a delay of 217 ms, a jitter of 55 ms, and no packet loss, which is better suited for evenly distributing bandwidth among users. Thus, HTB is recommended for priority-based networks, while PCQ supports fair bandwidth distribution across users.